A comparison of the ability of newly-developed bispyridinium oxime K203 and currently available oximes (trimedoxime, obidoxime, HI-6) to counteract the acute neurotoxicity of soman in rats - Kassa, Jiri; Karasova, Jana Zdarova; Tesarova, Sandra; Kuca, Kamil; Musilek, Kamil (Toxicology mechanisms and methods, 2010)
The neuroprotective effects of newly-developed oxime K203 and currently available oximes (trimedoxime, obidoxime, HI-6) in combination with atropine in rats poisoned with soman were studied. The soman-induced neurotoxicity was monitored using a functional observational battery at 24 h following soman challenge. The results indicate that the potency of a newly-developed oxime K203 to counteract soman-induced neurotoxicity is very low and roughly corresponds to the neuroprotective efficacy of currently available oximes. Among tested oximes, the oxime HI-6 seems to be the most efficacious to counteract acute neurotoxicity of soman, although the differences in neuroprotective efficacy of chosen oximes are not significant. Thus, the oxime K203 does not provide any beneficial effect for the antidotal treatment of acute poisoning with soman and the oxime HI-6 should be still considered to be the best oxime for antidotal treatment of acute soman poisonings.
Keywords: Animals; Chemical Warfare Agents; potkani Wistar; neurotoxické syndromy; Rats, Wistar; Neurotoxicity Syndromes; Atropine; oximy; Pyridinium Compounds; pohybová aktivita; pyridinové sloučeniny; chování zvířat; chemické bojové látky; Oximes; Male; Neuroprotective Agents; Soman; kombinovaná farmakoterapie; soman; krysa rodu Rattus; Behavior, Animal; Motor Activity; zvířata; mužské pohlaví; atropin; Rats; Drug Therapy, Combination; neuroprotektivní látky